The density of solutions to multifractional stochastic Volterra integro-differential equations. (January 2016) - Nguyen, Tien Dung
Abstract: The aim of this paper is to study the density of solutions to stochastic Volterra integro-differential equations with multifractional noises. We prove the existence of the density of solutions and show that the density is bounded by lower and upper Gaussian bounds.